Efficiency of indirect selection for grain yield in maize (Zea maysL.) under low nitrogen conditions through secondary traits under low nitrogen and grain yield under optimum conditions - Tadesse, Berhanu; Olsen, Michael; Das, Biswanath; Gowda, Manje; Labuschagne, Maryke T. (Springer, 2020)
Small-scale maize farmers in sub-Saharan Africa use meager amounts of nitrogen (N) in their maize crops. N use efficient varieties can provide a solution to the problem of low N conditions through efficient N uptake and utilization. The objectives of this study were to i) compare the quantitative genetic parameters of grain yield and secondary traits under different nitrogen levels and ii) assess the efficiency of indirect selection for grain yield under low N stress through yield under optimum N and secondary traits under low N stress in maize. Doubled haploid lines derived from five bi-parental populations were evaluated. Genotype effect for grain yield and secondary traits was significant at all sites. Genetic variance for grain yield was reduced by 17% under moderate N stress and 63% under severe N stress conditions, while genetic variance for days to anthesis and plant height increased under both moderate and severe low N stress. The heritability of most secondary traits was consistently higher than that of grain yield. Correlations of grain yield with plant and ear heights were positive under low N conditions. Despite the reduction in genetic variances under low N conditions, there was genetic variability for grain yield and secondary traits. Direct selection for grain yield under low N rather than under optimum conditions was more efficient for yield improvement under the low N condition. The use of an index of secondary traits could increase the efficiency of improving grain yield rather than selection for only grain yield under low N conditions.